Design and development of an experimental prototype of Chinese Tang Dynasty tomb murals under the intervention of digital media technology. (19th January 2023) - Jie, Guo; Chaetnalao, Atithep
This paper describes the design and development process of a digital interactive installation for Tang Dynasty tomb murals. It aims to provide the audience with a better situational experience, promote the interaction between cultural relics, the environment, and the audience, and effectively improve their visiting cognition. The research is experimental, and the experimental results are part of the researcher's doctoral dissertation. Focusing on the structure of ancient tombs and murals' content, the researchers integrated traditional Chinese culture's philosophical thought of 'harmony between man and nature' into digital media technology and reshaped the digital situational design. Relevant experts and audiences who participated in the questionnaire have recognised the design concept. Research shows that digital media design in museums enhances the audience's attention to cultural relics and directly affects the audience's visiting and interactive behaviour. The study affirms the importance of digital media art in museum situation design.